IMPLEMENTATION OF THE GENERAL PRINCIPLES OF GOOD GOVERNANCE IN ISSUING LICENSES IN THE REGENCY OF EAST LOMBOK - Kusmana, Lalu Dhedi (Jurnal IUS (Kajian Hukum dan Keadilan), 2013)
The comparative regulation of general principles of good governance in the laws and licensing related in Indonesia, to identify and assess the general principles of good governance which has been described in the licensing regulations in East Lombok and to analyze court decisions related dispute of application of general principles in good governance in the issuance of permits in eastern Lombok. By using statute approach, conceptual approach, comparative approach and case approach . The regulations of the general principles of good governance in the relevant licensing legislation in Indonesia is regulated in various ways with the terms and details of different . Furthermore, the regulations governing the licensing area in East Lombok has outlined eight general principles of good governance. While the procedures related to the issuance of permits in East Lombok is not yet fully guided by the general principles of good governance.Keywords : Application, General Principles of Good Governance and Licensing